HISTORY OF MODERN ISLAM IN IRAN AND THE IDEAS OF REFORMING THE AYATULLAH KOMAENI - Muslimah, Muslimah; Syukur, Syamzan; Susmihara, Susmihara (Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2023)
Modernism is a movement that originated in the western world to replace Catholic religious teachings with modern science and philosophy. The culmination of this movement is the process of secularization in the western world, before the revolution in Iran. The success of the Iranian Islamic Revolution which succeeded in overthrowing the Pahlavi dynasty which had changed the political system and form of the Iranian state from an absolute monarchy to an Islamic republic. A first popular revolution in the last quarter of the twentieth century against a modern authoritarian political system. However, this Iranian experience does not provide a definite answer to the problems between Islam and the originator of the Iranian revolution, Ayatollah Khomeini, who played a major role in moving the masses to carry out a revolution against the Pahlavi regime.